Rotary magnetic field combined with pipe fluid technique for efficient extraction of pumpkin polysaccharides. (June 2016) - Jin, Yamei; Yang, Na; Tong, Qunyi; Jin, Zhengyu; Xu, Xueming
Abstract: Pumpkin polysaccharides are considered as functional materials with bioactivities. However, the conventional aqueous extraction method for pumpkin polysaccharides is limited by long time consumption, low efficiency and potential damage to their bioactivities. To improve the efficiency of pumpkin polysaccharides extraction, we designed a new experimental system combining a rotary magnetic field and flowing conductive solution. Polysaccharide extractions by 1) acidic sample solution with agitation, 2) flowing acidic sample solution, 3) static magnetic field combined with flowing acidic sample solution, and 4) rotary magnetic field combined with flowing acidic sample solution were conducted at pH level of 2–4, temperature of 30–50 °C, and treatment time of 0–180 min. The extraction by use of rotary magnetic field combined with flowing acidic sample solution resulted in the highest polysaccharide yield. Then, the effects of rotational frequency, Reynolds number, pH, and temperature on extraction yield were investigated. The yield increased at first and then decreased with an increase in rotational frequency. The high polysaccharide yield was achieved at large Reynolds number, high temperature, and low pH. From the ultraviolet, Fourier transform-infrared spectrum and chromatographic analysis, the extracts proved to be polysaccharides with an average molecular weight of 1.435 × 10 5 Da. The extracted pumpkin polysaccharides exhibited a dose-dependent radical-scavenging capacity within 0.1 to 5 mg/mL in the order of hydroxyl radical > DPPH radical > superoxide radical. Industrial relevance: Rare report on the application of the combined magnetic field and pipe-fluid technique in extraction functional components from food materials. In this study, a novel experimental apparatus combining rotary magnetic field and spiral-pipe flow was designed to accelerate the extraction of pumpkin polysaccharides. In comparison with 1) agitation, 2) flowing acidic sample solution, and 3) static magnetic field combined with flowing acidic sample solution, the method combining rotating magnetic field and flowing acidic sample solution 4) significantly increased the polysaccharide yield. The increments were 40.18%, 32.14%, and 23.32%, respectively, after 180-min extraction. The pumpkin polysaccharides extracted by this novel method possessed a molecular weight of 1.435 × 10 5 Da and showed desirable antioxidant activities in vitro. Therefore, the combined magnetic field and pipe-fluid technique it is a potential method for efficient extraction of valuable compounds from food materials. Highlights: An efficient extraction system using varying magnetic flux was proposed. The yield was improved by rotary magnet field combined with pipe fluid. High Reynolds number is conducive to the increase of polysaccharide yield. The yield increased and then declined with the increase of rotational frequency.